Physical Culture and Sport in Soviet Society: Propaganda, Acculturation, and Transformation in the 1920s and 1930s - Brandon Miller (Slovo, 2013)
Physical Culture and Sport in Soviet Society: Propaganda, Acculturation, and Transformation in the 1920s and 1930s. By SUSAN GRANT. Pp. 260. New York and London: Routledge, 2013. £85.00. Hardback. ISBN: 9780415806954. Click here to read the review.